(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Acute Heart Failure in ST-Elevation Myocardial Infarction can occur in different age and gender. Objective: The purpose of the present study was to see the demographic characteristics of patients presented with acute heart failure in ST-elevation myocardial infarction. Methodology: This case-control study was conducted in the Department of Cardiology at National Institute of Cardiovascular Diseases, Dhaka, Bangladesh from February 2007 to July 2007. The patients admitted in the NICVD with ST-elevation acute myocardial infraction (STEMI) during study period were selected as study population. Patients presented with acute heart failure and patients developed acute heart failure within 24 hours of hospital admission were designed as case group. Patients with no feature of heart failure within 24 hours of hospital admission were designed as control group. Results: A total 186 patients with acute ST-elevation myocardial infarction were screened. Among them 60 patients were finally selected for this study. Of whom 30 were cases (patients with acute heart failure) and 30 were control (patients without heart failure). Patients needed severe cardiac massage and/or underwent DC shock at admission or before collection of blood sample for BNP testing were also excluded. About 70.0% of the cases and 60.0% of the controls were aged more than 50 years. About 80.0% cases of the subjects, both cases and control, were male and rests 20.0% cases were females. Male and female ratio was 4:1. Conclusion: In conclusion most of the patients are in the elder age group and male gender. Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):126-129